2011
DOI: 10.1177/0907568210394879
|View full text |Cite
|
Sign up to set email alerts
|

Social bundles: Thinking through the infant body

Abstract: Drawing on a UK research study on immunization, this article investigates parents' understandings of the relationship between themselves, their infants, other bodies, the state, and cultural practices - material and symbolic. The article argues that infant bodies are best thought of as always social bundles, rather than as biobundles made social through state intervention; and concludes that, while the natural/cultural divide may now be widely accepted as artificial within the social sciences, we need to scrut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…On the other hand, they also recognised that some exposure to infection was important for their infants' immune system to develop. They were pulled, therefore, between wanting to allow their babies to strengthen their immune system by some contact with germs and also experiencing a strong desire to protect them from illness via such contact (see Lauritzen 1997 andBrownlie andLeith 2011 for similar findings).…”
Section: Promoting Infants' Healthmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, they also recognised that some exposure to infection was important for their infants' immune system to develop. They were pulled, therefore, between wanting to allow their babies to strengthen their immune system by some contact with germs and also experiencing a strong desire to protect them from illness via such contact (see Lauritzen 1997 andBrownlie andLeith 2011 for similar findings).…”
Section: Promoting Infants' Healthmentioning
confidence: 98%
“…However it has been the focus of controversy, particularly in the UK, in relation to the alleged side effects of some vaccines (Polterak et al 2005, Hobson-West 2007, Brownlie and Leith 2011. While there has been less public debate over the risks of vaccination in Australia, it was clear from the women's accounts that many were aware of certain controversies and other issues concerning the value and safety of vaccinating infants.…”
Section: Immunisationmentioning
confidence: 99%
“…There is an intense governmentality of early childhood (N. Rose, 1990). As a result of the limited engagement from geographers and other critical social scientists (although see Brownlie & Leith, 2011;Gottlieb, 2000;Lupton, 2013), very early childhood remains largely the domain of child development psychologists, psychoanalysts and attachment theorists, particularly, as Moss and Petrie (2002) argue, within the Anglophone countries of the Global North (for exception see Keller, 2013;Olsson, 2010).…”
Section: Why Are Infants As Agents Largely Absent From Geography Andmentioning
confidence: 99%
“…However, to date, the sub-discipline, geography and, indeed, the wider social sciences (Brownlie & Leith, 2011;Lupton, 2013b) have tended to neglect the experiences of infants and very young children. The relative absence of very young children as research participants in geographies and social studies of children and youth is tied to the focus of those in the 'middle years of childhood'.…”
Section: Why Are Infants As Agents Largely Absent From Geography Andmentioning
confidence: 99%
“…Some European and British studies have examined more generally the ways in which mothers conceptualise and recognise good health and signs of illness in their infants and young children (BackettMilburn, 2000;Brownlie & Leith, 2011;Cunningham-Burley, 1990;Irvine & Cunningham-Burley, 1991;Lauritzen, 1997;Murcott, 1993). These studies demonstrated the strong sense of responsibility mothers felt for promoting their children's health, their view of children as vulnerable to illness, the importance they placed upon encouraging their children to engage in behaviours deemed health promoting and the ways in which they identified the signs of illness in their children.…”
Section: Introductionmentioning
confidence: 99%